Impact of Saccharomyces cerevisiae on the intestinal microbiota of dogs with antibiotic-induced dysbiosis - Arghavani, Sara; Chorfi, Younes; Segura, Mariela; Lesaux, Achraf Adib; Costa, Marcio C. (Frontiers in Veterinary Science, 2025)
IntroductionThe gut microbiota plays an important role in the health of dogs, but treatment with antibiotics causes marked dysbiosis. The objectives of this study were to evaluate the impact of yeast probiotic Saccharomyces cerevisiae supplementation on the fecal microbiota of dogs and its potential to prevent dysbiosis induced by antibiotics.MethodsTwenty healthy adult dogs were divided into a control and a yeast probiotic group receiving 1g/kg of S. cerevisiae (Actisaf®, Phileo by Lesaffre, Marcq-en-Barœul, France) daily from D0 to D31. Both groups were given oral metronidazole from D11 to D17. Fecal swabs were collected on D0, 3, 11, 17, 20, 24, and 31 for microbiota analysis and blood on D0 and D24 for measurements of cytokines and cortisol.Results and discussionAt D0, two distinct microbiota profiles comprised of dogs from both groups, control and probiotic, were identified. One profile had higher abundances of species related to stress and inflammation, and the other comprised species associated with good intestinal health. After three days of supplementation with yeast probiotic S. cerevisiae, all five dogs from the probiotic group having a stress-related microbiota (membership) shifted to a healthy microbiota. Metronidazole markedly changed the microbiota of both groups (p <0.001). Still, treated dogs had significantly different microbiota on D17 (end of antibiotics treatment). The dysbiosis was resolved in both groups by D24. TNF-α remarkably decreased from D0 to D24 (p = 0.002) in the probiotic group, which also had lower levels than controls on D24 (p = 0.040). There were no significant differences in the other measured cytokines. It was concluded that the use of yeast probiotic S. cerevisiae positively shifted the microbiota composition of healthy adult dogs carrying an abnormal microbial profile and that it has the potential to attenuate the dysbiosis caused by oral metronidazole.